Corneal confocal microscopy detects small fiber neuropathy in CMT1A patients - Tavakoli, Mitra (2012)
Although unmyelinated nerve fibers are affected in CMT1A, they have not been studied in detail due to the invasive nature of the techniques needed to study them. We established alterations in C-fiber bundles of the cornea in patients with CMT1A using non-invasive corneal confocal microscopy (CCM). Twelve patients with CMT1A and twelve healthy control subjects underwent assessment of neuropathic symptoms and deficits, electrophysiology, quantitative sensory testing, corneal sensitivity and corneal confocal microscopy. Corneal sensitivity, corneal nerve fiber density, corneal nerve branch density, corneal nerve fiber length and corneal nerve fiber tortuosity were significantly reduced in CMT1A patients compared to controls. There was a significant correlation between corneal sensation and CCM parameters with the severity of painful neuropathic symptoms, cold and warm thresholds and median nerve CMAP amplitude. CCM demonstrates significant damage to C-fiber bundles, which relates to some measures of neuropathy in CMT1A patients.